Prevalence and antimicrobial resistance of Listeria, Salmonella, and Yersinia species isolates in ducks and geese - Jamali, H.; Radmehr, B.; Ismail, S. (Oxford University Press, 2014)
The aims of this study were to determine the prevalence and antimicrobial resistance of Listeria, Salmonella, and Yersinia spp. isolated from duck and goose intestinal contents. A total of 471 samples, including 291 duck and 180 goose intestinal contents, were purchased from wet markets between November 2008 and July 2010. Listeria, Salmonella, and Yersinia spp. were isolated from 58 (12.3%), 107 (22.7%), and 80 (17%) of the samples, respectively. It was concluded that Listeria ivanovii, Salmonella Thompson, and Yersinia enterocolitica were the predominant serovars among Listeria, Salmonella, and Yersinia spp., respectively. Moreover, resistance to tetracycline was common in Listeria (48.3%) and Salmonella spp. (63.6%), whereas 51.3% of the Yersinia spp. isolates were resistant to cephalothin. Therefore, continued surveillance of the prevalence of the pathogens and also of emerging antibiotic resistance is needed to render possible the recognition of foods that may represent risks and also ensure the effective treatment of listeriosis, salmonellosis, and yersiniosis.